The Influence of Work Stress on Employee Performance at Hotel Aloft Bali Seminyak - Linda, Tina; Harefa, Mega Hernawaati; Febria, Devia; Kelana, Jimmi; Siboro, Lidya Berliana (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to assess the influence of work-related stress on staff performance at the Aloft Bali Seminyak Hotel. The research employs a quantitative methodology, especially utilizing a survey approach. The study population comprised randomly selected workers from the Aloft Bali Seminyak Hotel. We collected data using a questionnaire that included questions on work-related stress levels and employee performance evaluations. Regression techniques were utilized to evaluate the data and determine the link between job stress characteristics (independent factors) and employee performance (dependent variables). The study's results indicated a significant relationship between occupational stress levels and employee performance. The findings indicate that increased work-related stress adversely impacts staff performance at the Aloft Bali Seminyak Hotel. This study significantly enhances our comprehension of the factors influencing employee performance in the hospitality industry, specifically inside luxury hotels such as the Aloft Bali Seminyak Hotel. This study's practical implications necessitate that hotel management focus work stress management to improve employee performance and create a robust, efficient work environment. This might substantially improve institutional performance.